A potential novel treatment strategy: inhibition of angiogenesis and inflammation by resveratrol for regression of endometriosis in an experimental rat model. (March 2015) - Ozcan Cenksoy, Pinar; Oktem, Mesut; Erdem, Ozlem; Karakaya, Cengiz; Cenksoy, Cahit; Erdem, Ahmet; Guner, Haldun; Karabacak, Onur
Abstract The aim of our study was to evaluate the effectiveness of resveratrol in experimentally induced endometrial implants in rats through inhibiting angiogenesis and inflammation. Endometrial implants were surgically induced in 24 female Wistar–Albino rats in the first surgery. After confirmation of endometriotic foci in the second surgery, the rats were divided into resveratrol (seven rats), leuprolide acetate (eight rats), and control (seven rats) groups and medicated for 21 d. In the third surgery, the measurements of mean areas and histopathological analysis of endometriotic lesions, VEGF, and MCP-1 measurements in blood and peritoneal fluid samples, and immunohistochemical staining were evaluated. After treatment, significant reductions in mean areas of implants (p < 0.01) and decreased mean histopathological scores of the implants (p < 0.05), mean VEGF-staining scores of endometriotic implants (p = 0.01), and peritoneal fluid levels of VEGF and MCP-1 (p < 0.01, for VEGF and p < 0.01, for MCP-1) were found in the resveratrol and leuprolide acetate groups. Serum VEGF (p = 0.05) and MCP-1 (p = 0.01) levels after treatment were also significantly lower in the resveratrol and leuprolide acetate groups. Resveratrol appears to be a potential novel therapeutic agent in the treatment of endometriosis through inhibiting angiogenesis and inflammation. Further studies are needed to determine the optimum effective dose in humans and to evaluate other effects on reproductive physiology.